2019
DOI: 10.1101/547596
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unique and assay specific features of NOMe-, ATAC- and DNase I-seq data

Abstract: Chromatin accessibility maps are important for the functional interpretation of the genome. Here, we systematically analysed assay specific differences between DNase I-Seq, ATAC-Seq and NOMe-Seq in a side by side experimental and bioinformatic setup. We observe that most prominent nucleosome depleted regions (NDRs, e.g. in promoters) are roboustly called by all three or at least two assays. However we also find a high proportion of assay specific NDRs that are often “called” by only one of the assays. We show … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 76 publications
(74 reference statements)
0
5
0
Order By: Relevance
“…Several previous studies showed that open chromatin regions identified by DNase I and Tn5 largely overlap in both animal and plant species [6,63,64]. We demonstrate that MH-seq reads cover the majority of the open chromatin regions identified DNase-seq and ATAC-seq.…”
Section: Discussionmentioning
confidence: 49%
“…Several previous studies showed that open chromatin regions identified by DNase I and Tn5 largely overlap in both animal and plant species [6,63,64]. We demonstrate that MH-seq reads cover the majority of the open chromatin regions identified DNase-seq and ATAC-seq.…”
Section: Discussionmentioning
confidence: 49%
“…The nucleosome occupancy and methylome sequencing assay. For the nucleosome occupancy and methylome sequencing (NOMe-seq) assay, we adapted current protocols 34,56 . A detailed experimental procedure can be found at https:// www.protocols.io/view/nome-seq-of-fixed-cells-brdwm27e.…”
Section: Rna Extraction Real-time Quantitative Pcr and Rna-seq Librar...mentioning
confidence: 99%
“…Textbooks describe gene inactivation by a hierarchical chromatin folding from open 10nm fibres to condensed and higher occupied 30nm filaments. Active transcription accompanied by open, accessible chromatin in mammals was highly supported in the last years by many studies of DNA accessibility using ATAC, NOMe, DNAse-Seq or methods free of enzymatic steps like sedimentation velocity centrifugation [30,34,45]. Our data does not support this model for Paramecium Mac chromatin suggesting a totally different chromatin associated mechanism of gene inactivation.…”
Section: Genomic and Epigenomic Paradoxesmentioning
confidence: 52%